Cognitive Science and Health Bioinformatics Advances and Applications - Korrapati, Raghu B.; Divakar, Ch; Devi, G. Lavanya (SpringerBriefs in Forensic and Medical Bioinformatics, 2018)
This book highlights the interdisciplinary study of cognition, mind and behavior from an information processing perspective, and describes related applications to health informatics. The respective chapters address health problem-solving and education, decision support systems, user-centered interfaces, and the design and use of controlled medical terminologies. Reflecting cutting-edge research on computational methods - including theory, algorithms, numerical simulation, error and uncertainty analysis, and their applications - the book offers a valuable resource for doctoral students and researchers in the fields of Computer Science and Engineering.